Menakar Kualitas Penalaran Hukum dalam Putusan Pengadilan Tata Usaha Negara Kupang Nomor 41/G/2022/PTUN.KPG - Tontji Christian Rafael; Rian Van Frits Kapitan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The focus in this article is: why did the Panel of Judges exclude the requirement to submit an administrative objection before filing a lawsuit in the Kupang State Administrative Court decision Number: 41/G/2022/PTUN.KPG, dated 28 October 2022? and what is the quality of the legal reasoning of the Panel of Judges in excluding the need to submit administrative objections before filing a lawsuit in the decision of the Kupang State Administrative Court Number: 41/G/2022/PTUN.KPG, dated 28 October 2022 2022?. The reason the Panel of Judges excluded the requirement to submit an administrative objection before filing a lawsuit in the decision of the Kupang State Administrative Court Number: 41/G/2022/PTUN.KPG, dated 28 October 2022 was based on several things, firstly the filing of an administrative objection by the Plaintiff had already passed and was impossible can be repeated so that the calculation of the deadline for filing administrative objections is no longer possible for the Plaintiff. Second, substantial legal facts were found which could invalidate the object of the dispute so that the formality provisions of the lawsuit regarding time limits and administrative efforts in the dispute had to be set aside. The authors also conclude that the legal reasoning of the Panel of Judges in excluding the need to submit administrative objections before filing a lawsuit in the Kupang State Administrative Court decision Number: 41/G/2022/PTUN.KPG, dated 28 October 2022 is not logical and perfect.